Efektivitas Pelayanan Publik Pada Kantor Camat Kecamatan Mazino Kabupeten Nias Selatan Provinsi Sumatera Utara - Loi, Takdir; Jamil, Bahrum (Universitas Medan Area, 2025)
Effective public service is a key pillar in realizing good governance. However, its implementation at the sub-district level still faces various challenges. This study aims to analyze the effectiveness of public service delivery at the Mazino Sub-District Office, South Nias Regency, and to identify existing obstacles and improvement efforts. Using a qualitative approach with an empirical juridical method, data were collected through observation, in-depth interviews, and documentation. The research findings indicate that the effectiveness of public services still requires improvement to be more aligned with South Nias Regency Regulation No. 12 of 2017. Several aspects, such as the simplicity of procedures, timeliness, fairness of services, and transparency, continue to face challenges in their implementation. This condition suggests the need for continuous efforts to enhance service mechanisms so that they can better meet the needs and expectations of the community. The identified research gap lies in the lack of empirical studies linking the implementation of regional regulations to the quality of services at the sub-district level. This study contributes by providing contextual insights into the structural and operational barriers affecting public service quality. Its practical implications emphasize the need to strengthen supervision, enhance the capacity of government personnel, and conduct continuous public outreach to promote more responsive, fair, and accountable local public services.